Innovative therapeutic pants for children with genu varum and genu valgum - Pristiyani, Kurnia; Solikhah, Umi; Mahesaputra, Renaldi; Al Hamra, Falah Dinar (Universitas Muhammadiyah Purwokerto, 2019)
Background: This research is motivated by the absence of therapeutic pants in patients with genu deformity, so innovations to create latest medical products are needed to prevent the disease. One of the innovations is development of therapeutic pants for genu varum and genu valgum. Objective: It aims to research and develop therapeutic pants to improve comfort of children with genu varum and genu valgum.Methods: This study used Research and Development (R&D) approach. It consisted of 3 phases, namely phase I, II, and III or product trials.Result: From the literary study in phase I, it was obtained that materials used to make the therapeutic pants were cotton cloth fabric and foam. In the second phase of the research, it was also discovered that designs and shapes of the pants were as needed. The results of product trials or phase III of this study involved 5 respondents; it showed that the use of therapeutic pants in toddlers resulted comfort and satisfaction for them.Conclusion: The therapeutic pants are proven to increase comfort in toddlers with genu varum and genu valgum.